IMPROVING STUDENT APPRECIATION ON TRADITIONAL MUSIC TOOLS IN BASIC SCHOOL THROUGH THE SARON DIGITAL APPLICATION - Apriani, Lestari; Sunarya, Dede Tatang; Julia, Julia (Jurnal Pena Ilmiah, 2019)
The lack of learning media facilities for traditional musical instruments in extracurricular music is one of the reasons for the lack of appreciation of students for traditional musical instruments in elementary schools. The purpose of this study is to increase students' appreciation of traditional musical instruments through the application of Saron Digital applications as interactive learning media that can be used in music extracurricular activities. This study uses qualitative methods with research design, namely action research. The subjects who participated in this study were as many as 10 students consisting of grades three to six who participated in music art extracurricular activities at Mandalaherang II Elementary School. The research subjects consisted of eight female students and two male students who were domiciled in Mandalaherang Hamlet, Cimalaka District, Sumedang Regency. The results obtained in this study are that there is an increase in students' appreciation of traditional musical instruments can be proven by an increase in love for traditional musical instruments which initially only 30% after being given the action to 90%. Thus the application of the Digital Sarl application to extracurricular learning in the art of music can be one solution to increase students' appreciation and interest in traditional musical instruments.